2016
DOI: 10.1177/0954405416666903
|View full text |Cite
|
Sign up to set email alerts
|

Social manufacturing as a sustainable paradigm for mass individualization

Abstract: With increasing product personalization and open innovation, the manufacturing paradigm has been transforming to a more decentralized and socialized one. Social manufacturing was proposed as a new paradigm for industry. It extends the crowdsourcing idea to the manufacturing area. By establishing cyber–physical–social connection via decentralized social media, various communities can be formed as complex, dynamic autonomous systems to co-create customized and personalized products and services. This article pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(38 citation statements)
references
References 18 publications
0
37
0
1
Order By: Relevance
“…3-D printing is being used by ordinary people who have little technical knowledge to create their own custom products [55]. This is mass individualization [56], which provides the largest benefit of distributed manufacturing; the ability for users to customize products for their needs. This study demonstrated the ability to do this with the customization of EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…3-D printing is being used by ordinary people who have little technical knowledge to create their own custom products [55]. This is mass individualization [56], which provides the largest benefit of distributed manufacturing; the ability for users to customize products for their needs. This study demonstrated the ability to do this with the customization of EBPs.…”
Section: Discussionmentioning
confidence: 99%
“…This article is concerned with the re-combination of existing actors with new ones as a way to contribute different kinds of human (social and cultural) capital to making processes, using local resources and skills wisely and shortening the value chain (Fuad-Luke, 2011). Moreover, the term social manufacturing is referred to as a democratic approach to opening the design and manufacturing phase to everyone (Shang et al, 2013) and it has mainly been used so far in relation to digitally-enabled personal fabrication, or mass customisation and distributed manufacturing (Leng, Ding, Gu, and Koren, 2016;Hämäläinen and Karjalainen, 2017). Instead, in this article we prefer using the term social making to emphasise the 'social' aspect of collaboration and interaction at a local level, through alternative design strategies based on analogical, small-scale and local production systems.…”
Section: Alternative/diverse Fashion Practices Of Exchange and Value mentioning
confidence: 99%
“…A systematic designing of AFMS suffers from three major problems. First, since the mass individualisation paradigm deeply affects manufacturing logic (Gao et al 2011;Jiang et al 2016), the flexibility of AFMS design has to be improved so downtime and delay can be prevented (Yang et al 2015). Second, the designers need to find optimal configurations by evaluating multiple design variables (e.g., equipment selection, control scheme and WIP flow) and considering different forms of manufacturing uncertainties (e.g., machine breakdowns, processing times and product demands).…”
Section: Introductionmentioning
confidence: 99%